The Implementation of Project-Based Learning in Indonesian EFL Class Between 2017 to 2022: A Systematic Review - Halim, Nixon; Boys, Melkisedek; Fahmi, Farid; Nitin, Mahon (Yayasan Pedidikan Islam Daarut Thufulah, 2023)
The project-based learning (PjBL) approach emphasizes the learning process, which has a tangible endpoint in the form of a product, and makes students the subject or focal point of instruction. In other words, students are free to choose their educational pursuits and to collaborate on learning tasks until a finished product is produced. Because of this, the degree to which students participate in their education has a significant impact on its success. A systematic review was used as the research methodology to analyze the literature across 15 journals using data from several databases, including Garuda and Google Scholar. The journals were analyzed utilizing a content analysis method and the data are presented in systematic diagrams and tables. The result of the study revealed that Project-based learning (PjBL) was the most used at University with 60% and between 2017-2022. In 2022 was the most popular Project-based learning very high. In addition, research methods in project-based learning were quantitative and qualitative in the same amount. Moreover, the most implemented Project-based learning was to increase speaking and vocabulary skills. Further analysis of advantages related to the use of Project-based was also illustrated.